Independent Non-Executive Directors, Managerial Ownership and Firm Performance in Malaysian Public Listed Companies - Kanapathy, K. Vethanayagam (2005)
Leung and Horwitz (2004) argued that the failing of corporate governance and lack of transparency are often associated with the Asian financial crisis. Therefore, this study attempt to examine the relationship between independent non-executive directors and managerial ownership towards firm performance, as measured by Tobin’s Q.